(untitled) (World Bulletin of Management and Law, 2022)
The article analysed the changes in quantitative and qualitative indicators of the development of the world food market. The main trends in the world market of food products and indicators of the development of food products markets related to the influence of marketing and state policy on quality and quantity indicators in different countries were determined. The development of special areas of the world food market, including the collection of wild plants and the consumption of food products in public catering systems, was considered. The characteristics of the current situation in the food products market of Uzbekistan are given. Arguments are presented in favour of further development of the food products market of Uzbekistan